Selective harmonic control: a general problem formulation and selected solutions - Wells, J.R.; Nee, B.M.; Chapman, P.L.; Krein, P.T. (IEEE transactions on power electronics, 2005)
Selective harmonic elimination/control has been a widely researched alternative to traditional pulse-width modulation techniques. Previous and current work has made fundamental assumptions that enforce output waveform quarter-wave symmetry, presumably in order to reduce the complexity of the resulting equations. However, the quarter-wave symmetric assumption is not strictly necessary. It restricts the solution space, which can result in sub-optimal solutions with regards to the uncontrolled harmonic distribution. A more general formulation is proposed, removing the quarter-wave symmetry constraint for two classes of the m-level, n-harmonic harmonic control problem. The special cases of two- and three-level harmonic elimination are presented in detail along with representative solutions for each harmonic control problem. New solutions previously unattainable based on quarter-wave symmetric techniques are identified.